1998
DOI: 10.1016/s0005-2728(98)00111-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the mitochondrial permeability transition as a mechanism of liver injury during cholestasis: a potential role for mitochondrial proteases

Abstract: As part of this thematic series on mitochondria in cell death, we would like to review our data on: (1) the role of the mitochondrial permeability transition (MPT) in hepatocyte necrosis during cholestasis; and (2) the concept that endogenous mitochondrial protease activity may lead to the MPT. Many chronic human liver diseases are characterized by cholestasis, an impairment in bile flow. During cholestasis an accumulation of toxic hydrophobic bile salts in the hepatocyte causes necrosis. We tested the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 25 publications
3
83
1
Order By: Relevance
“…However, at lower concentrations (: 50 mM), bile acids may alter cell function by interfering with intracellular signaling mechanisms (Rust et al, 2000) and mitochondrial membrane permeability (Gores et al, 1998;Rolo et al, 2000). Regardless, cholestasis due to accumulation of bile acids has been thought to reflect the direct cytotoxicity of the individual bile acids (Kaplan, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at lower concentrations (: 50 mM), bile acids may alter cell function by interfering with intracellular signaling mechanisms (Rust et al, 2000) and mitochondrial membrane permeability (Gores et al, 1998;Rolo et al, 2000). Regardless, cholestasis due to accumulation of bile acids has been thought to reflect the direct cytotoxicity of the individual bile acids (Kaplan, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…In order to provide new insights into the understanding of the effects of therapeutic bile acids, in vitro studies have been done. Several reports described a role for the putative beneficial effect of UDCA exerted at the level of mitochondrial function, where UDCA prevents the impairment of mitochondrial function induced by toxic bile acids (Gores et al, 1998;Rodrigues et al, 1998). It has also been reported that UDCA could exert a cytoprotective action related to oxidative injury and antioxidant systems (Mitsuyoshi et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of the MPT, characterized by large amplitude swelling and loss of the electrochemical potential across the inner mitochondrial membrane (8,9), leads to release of cytochrome c and apoptosis-inducing factor into cytosol, activating downstream caspases and cellular apoptosis (10). The role of the MPT in bile acid-induced hepatocyte necrosis and apoptosis has recently been established (11)(12)(13)(14)(15). Evidence from several laboratories indicates that stimulation of the MPT by bile acids is commensurate with increased generation of ROS (7,11,14,15) and that oxidative modification of the MPT pore may mediate its opening (16).…”
mentioning
confidence: 99%
“…Moreover, the mitochondria are a source of a number of the Bcl-2 family members and, in lymphoid cells, of the apoptosis inducing factor, a protein associated with opening of the pore and induction of apoptosis (10). Other mitochondrial factors that are associated with liver apoptosis in vivo are proteases that are released during cholestasis (11). Finally several studies showed that after induction of apoptosis mitochondria release cytochrome c (12), which is associated with opening of the mitochondrial pore (13).…”
mentioning
confidence: 99%